2006
DOI: 10.1128/jcm.00801-06
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Rabies Virus Isolates in India

Abstract: In India, rabies is enzootic and is a serious public health and economic problem. India has a large population of stray dogs which, together with a lack of effective control strategies, might have led to the persistence of rabies virus (RV) in the canine population. Our objective was to study the molecular epidemiology of RV isolates in India based on nucleotide sequence analysis of 29 RV isolates originating from different species of animals in four states. Here we have analyzed two sets of sequence data base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 39 publications
5
36
0
Order By: Relevance
“…This study was undertaken to characterize the rabies virus isolates of Indian origin through nucleotide sequencing of partial N and P genes. As of now, a very limited number of studies have examined the molecular epidemiology of rabies viruses circulating in India by sequence analysis of the glycoprotein-cytoplasmic domain (G-CD) region, the noncoding G-L intergenic region, partial L sequence and the full length genome [6][7][8]. In this study, the genetic relatedness of rabies virus isolates from across India and between rabies viruses of other parts of the world have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…This study was undertaken to characterize the rabies virus isolates of Indian origin through nucleotide sequencing of partial N and P genes. As of now, a very limited number of studies have examined the molecular epidemiology of rabies viruses circulating in India by sequence analysis of the glycoprotein-cytoplasmic domain (G-CD) region, the noncoding G-L intergenic region, partial L sequence and the full length genome [6][7][8]. In this study, the genetic relatedness of rabies virus isolates from across India and between rabies viruses of other parts of the world have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…This has been explained by Denduangboripant et al [43] who suggested that transmission of rabies virus may be related to availability of transportation routes, human activity particularly human migration as well as human and animal population density. Genomic heterogeneity of nucleoprotein and glycoprotein among various rabies viruses isolated from different geographical regions and several sources including human, dog, cat, cattle, and sheep has been reported previously [13,14,26].…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies have undertaken the molecular characterization of the rabies strains circulating in India. More recently, phylogenetic analyses based on the partial nucleoprotein gene sequences have been reported [13,14]. However, to date, no complete genome sequence analysis and characterization of an Indian rabies virus isolate has been undertaken.…”
Section: Introductionmentioning
confidence: 98%
“…Lack of comprehensive rabies control programs and an inability to pay for post exposure treatments after dog bites are responsible for high incidences of rabies in Asian countries (Knobel et al, 2005;Wilde et al, 2007). Over the past decade many molecular epidemiological studies have been conducted in Asian countries, and have provided a better understanding of the RABV variants circulating in Asia and the transmission dynamics of the disease (Denduangboripant et al, 2005;Nanayakkara et al, 2003;Nagarajan et al, 2006;Susetya et al, 2008;Gong et al, 2010;Hyun et al, 2005). This information is needed for implementation of effective rabies control programs in the region.…”
Section: Lagos Bat Virus (Lbv) Mokola Virus (Mokv) Rabies Virus (Ramentioning
confidence: 99%